家長網路管教、學校投入與青少年危險網路行為之關係：家庭凝聚力之調節效果分析 Relationships Between Parental Internet Intervention, School Engagement, and Risky Online Behaviors Among Adolescents: The Moderatoring Role of Family Cohesion - 林漢唐 Han-Tang Lin; 陳慧娟 Huey-Jiuan Chen (National Taiwan Normal University, 2016)
本研究旨在瞭解家長網路管教、家庭凝聚力、學校投入、學校不熱衷與青少年危險網路行為的關係，並探討家庭凝聚力在家長網路管教與危險網路行為之調節作用。調查對象為臺灣本島與離島地區，公私立國中七、八、九年級共1,006位學生。研究工具包括自編之「危險網路行為量表」與「家長網路管教量表」，以及編修之「家庭凝聚力量表」與「學校投入與學校不熱衷量表」。主要研究結果如下：一、在本研究樣本中，近半數青少年曾在網路上進行過一項以上的危險活動；二、年級愈高，危險網路行為比例普遍增加；三、青少年持有個人智慧型手機者，出現危險網路行為的程度高於未擁有者；四、「家長監控」、「學校行為不熱衷」和「情感不熱衷」與青少年從事危險網路活動有正相關；五、「家長限制」、「家庭凝聚力」、「學校行為投入」及「情感投入」則與青少年危險網路行為有負相關；六、「學校不熱衷」對青少年危險網路行為的預測效果最明顯，其次依序為「家長監控」、「家長限制」，以及「家庭凝聚力」；七、「家庭凝聚力」對「家長網路管教」、「學校投入」與「危險網路行為」之關係具有調節效果。具體而言，在「家庭凝聚力」非常連結的情況下，「家長限制」和「學校投入」對其「危險網路行為」具有顯著的負向解釋力。而對於知覺家庭凝聚力疏離的國中生，「家長監控」對「危險網路行為」的正向解釋力高於非常連結之國中生。針對本研究發現整理出各項具體建議，提供教育實務及未來研究的參考。 The purpose of this study was to examine the relationships between risky online behaviors, parental Internet intervention, family cohesion, school engagement among adolescents. Family cohesion was also tested as a moderator in the relationship between parental Internet intervention and risky online behavior. The participants of this study were 1,006 junior high school students in Taiwan, and included participants from offshore islands. Self-made scales were used, namely the Risky Online Behavior Scale, Parental Internet Intervention Scale, Family Cohesion Scale, and School Engagement Scale. The main findings of the study are as follows: (1) Nearly half of adolescents showed at least one online risky behavior; (2) Upper grade students scored higher than lower grade students in all types of risky online behaviors; (3) Smartphone owners showed higher levels of risky online behaviors in passive cyberbullying, making Internet friends, Internet stickiness addiction, online pornography, and online privacy intrusion than nonowners did; (4) Risky online behavior was associated significantly with parental monitoring, behavioral disengagement, and emotional disaffection in school; (5) Significant and negative relationships were found between parental restriction, family cohesion, behavioral engagement and emotional engagement in school, and online risky behavior; (6) The strongest predictor for adolescent risky online behavior was school disaffection, followed by parental monitoring, restriction, and family cohesion; (7) The relationships between parental Internet intervention, school engagement, and risky online behaviors among adolescents were moderated by family cohesion. On the basis of the findings of this study, suggestions are presented for schools, families, and future research.